CHARACTER EDUCATION IN KH ZAINAL MUSTOFA'S PERSPECTIVE AND ITS RELEVANCE TO THE NATIONAL EDUCATION GOALS - Amin, Sulthan Zainul; Alhubilah, Fahmi; Istiqomah, Salma Nur; Sauri, Sofyan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Character education is an important aspect in the formation of a generation with integrity, responsibility and high morals. This article analyzes the perspective of character education according to KH Zainal Mustofa and its relevance to the goals of national education in Indonesia. Based on a qualitative approach and literature study, this research identifies three main pillars in KH Zainal Mustofa's character education, namely spiritual, social, and personal ethics values. Spiritual values emphasize man's relationship with God as the basis of morality, social values encourage social awareness and solidarity, and personal ethics values instill discipline, honesty, and hard work. These three pillars are in line with the objectives of national education which focus on the formation of people of faith, responsibility and noble character. The findings of this study indicate that KH Zainal Mustofa's character education approach can be used as a model in the development of character education policies in Indonesia, by emphasizing the balance between religious values and worldly needs. Therefore, this approach provides an important contribution in the development of character education that is relevant to the challenges of the times.